Zihan Hulinggato - Zihan Hulinggato; Zamroni Abdussamad; Janwar Hippy (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
This study examines the disharmony between Gorontalo City Regional Regulation No. 1 of 2018 on Public Order and Mayoral Regulation No. 4 of 2010 on nighttime entertainment operations. Although regulating similar matters, the two instruments lack coherence, causing uncertainty in implementation, particularly in Leato Selatan Village. The research employs a normative legal method through statutory and conceptual approaches, supported by interviews with relevant authorities. The findings reveal vertical, substantive, normative, and hierarchical inconsistencies resulting from weak institutional coordination, inadequate legislative scrutiny, and outdated provisions. This disharmony is both normative and structural, indicating deficiencies in the regional legislative framework. Accordingly, reform is necessary, including revising the Mayoral Regulation, strengthening inter-institutional cooperation, and enhancing the role of legislative drafters to ensure coherent, adaptive, and socially responsive regulations.